POLA DAN PEMBENTUKAN PERSAJAKAN SYAIR SURAT KAPAL - Yulita Fitriana (Balai Bahasa Provinsi Riau, 2015)
The poem Surat Kapal that exists in the society of Indragiri Hulu, Riau has various pattern of poetry. In this research, the issue raised is how about the pattern and the way to construct the poetry of Surat Kapal. The aim of this research is to identify the pattern and the way how to construct the poem. Theory used is the structuralism theory that see a literary work as a structure. This research is descriptive qualitative. The data used is the secondary data that taken from books and poems that written by readers in Surat Kapal. Through this research, it is known that the formation of this poem is carried out by 1) word choice (diction) and the word choice that has similar end phoneme, 2) syllables repetition or the same words, 3) the conversion of sentence structure, 4) code mixing in another language (Indonesian language and regional language), 5) the removal of letters, and 6) the addition -nya (-nye) and -k.